2021
DOI: 10.1002/admt.202101033
|View full text |Cite
|
Sign up to set email alerts
|

Label‐Free Cell Migration Assay Using Magnetic Exclusion

Abstract: biophysical cues. [1,2] Signaling molecules regulate cell migration under normal physiological conditions by controlling cell adhesion and cytoskeleton organization. [1,3,4] Conversely, pathological conditions such as metastatic cancer, vascular disease, and chronic inflammation are associated with unregulated cell migration, contributing to disease progression. [4,5] The wound healing assay is a commonly used in vitro method to study cell migration, cell interactions, and the underlying mechanisms. [6][7][8][… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…For former research generating cellular patterns on substrates, it is still hard to prepare patterns with micrometer size. The throughput of cell assembly is also limited as only a few assemblies were able to prepare at the same time . In our system, we were about to prepare a hundred microscale cell assemblies in one square centimeter in batches (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For former research generating cellular patterns on substrates, it is still hard to prepare patterns with micrometer size. The throughput of cell assembly is also limited as only a few assemblies were able to prepare at the same time . In our system, we were about to prepare a hundred microscale cell assemblies in one square centimeter in batches (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…In most of the abovementioned research, magnets were used to generate a power source for cell magnetic levitation, the patterns being generated by self-assembly of cells. Puri et al 21 generated a controllable cell exclusion area by using magnetic levitation. However, limited by the size of permanent magnets, only a few simple constructs have been fabricated using the Mag-Arch strategy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that Gadavist exposure has insignificant effects on HBEC3 KT viability . The impact of Gadavist exposure on primary fibroblast metabolism, an indicator of viability, is investigated using a resazurin-based assay (Presto Blue HS).…”
Section: Resultsmentioning
confidence: 99%
“…Since cell receptor complexes for OSM and IL6 have a common glycoprotein 130 (gp130) signal transduction chain, we stimulate HBEC3 KT with IL6 to determine whether this cytokine has similar effects on the cell dynamics as OSM . EGF is used as a positive control, as we have previously demonstrated enhanced HBEC3 KT migration due to EGF (0.8 ng mL –1 ) exposure . The annular aggregates are assembled on tissue culture-treated (TCT) and ECM-coated surfaces within 3 h to assess the impact of surfaces on cell-free area closures.…”
Section: Introductionmentioning
confidence: 99%